Alexithymia in Parkinson's disease: A systematic review of the literature. (July 2016) - Assogna, Francesca; Cravello, Luca; Orfei, Maria Donata; Cellupica, Nystya; Caltagirone, Carlo; Spalletta, Gianfranco
Abstract: Introduction: In this systematic review, we aimed to evaluate the role of alexithymia in Parkinson's disease (PD) and its relationship to neurological, neuropsychiatric, cognitive, and neuroimaging correlates. Methods: The database was selected using PubMed Services, Cochrane, PsycNET and Scopus and a number of key words. Further studies were sought by manually searching for secondary sources, including relevant journals and references in primary articles. The search was restricted to articles written in English between January 1980 and August 2015. Results: Ten studies reported that alexithymia prevalence was about double in PD patients compared to control subjects and that specific dimensions of alexithymia might be related to depression, anxiety, apathy and impulsivity. Some studies investigated the relationship between alexithymia and neuropsychological symptoms and found correlations with frontal and parietal lobe functions. Two studies on neurological features reported a link between alexithymia and disease stage or a specific motor subtype of PD; the remaining studies found that alexithymia was independent from neurological symptoms, dopaminergic therapy and laterality of motor symptom onset. Data on neuroimaging correlates and therapeutic intervention on alexithymia in PD patients are still lacking. Conclusion: Although results suggest that alexithymia is a primary characteristics of PD, further studies with larger patient samples are needed to definitively clarify the impact of alexithymia on the clinical features of PD patients. Highlights: Alexithymia may lead to poorer quality of life and reduced social interactions. Alexithymia prevalence is about double in PD patients than control subjects. Alexithymia could be related to depression, anxiety, apathy and impulsivity. It is associated with disrupted empathetic processes. It could constitute an early premotor diagnostic aid for PD.